Decongesting the dodgy hub: the role of mass media in curtailing illicit drug trafficking and use in Nigeria (2015)
"Trafficking and use of illicit drugs have become a deadly plague unleashing social and health hazards on the human race. The problem is more prevalent in the developing nations, while Nigeria is one of the most affected African countries. The United Nations Office on Drugs and Crime (UNODC) has acknowledged this fact. Despite efforts by the Nigerian anti-drug abuse agencies, the rate of drug-related crimes in the country seems to persist. This paper, after presenting some statistics on the prevalence of drug problems in Nigeria, suggests that the nation’s mass media should be more aggressively involved in fighting trafficking and use of illicit drugs in the country. With the Agenda-Setting theory as the theoretical framework, the paper discusses different social change strategies that the Nigerian mass media could adopt to fight drug-related vices. However, the researchers recommend that these media campaigns should be effectively complemented with other communication approaches. "